Charting a new course in medical rehabilitation sciences - Al-Otaibi, Hajed (J Med Rehab Sci, 2025)
The need to improve the quality of life and address current challenges in medical rehabilitation has increased the demand for new journals in the field of medical rehabilitation sciences. There is also a growing need for high-quality, peer-reviewed research in rehabilitation sciences to address these issues adequately. We are, therefore, delighted to present the inaugural issue of a newly established healthcare journal. The Journal of Medical Rehabilitation Sciences (J Med Rehab Sci), sponsored by the Faculty of Medical Rehabilitation Sciences at King Abdulaziz University, is a peer-reviewed publication designed to make significant contributions to the enrichment of knowledge and improvement of healthcare services within the scope of medical rehabilitation. It is hoped that this scientific contribution will lead to better healthcare services and improved patient outcomes. The J Med Rehab Sci aims to provide a platform for valuable and landmark research, shaping the future of medical rehabilitation. More importantly, the journal also aims to foster interdisciplinary collaboration and enhance evidence-based medicine. All categories of medical rehabilitation research, encompassing various disciplines such as physical therapy, occupational therapy, respiratory therapy, speech and communication disorders, audiology, prosthetics, and orthotics, among others, are considered within the scope of J Med Rehab Sci. This journal welcomes both fundamental and clinical research, with a particular emphasis on translational research to bridge the gap between laboratory findings and clinical application. Authors can submit their manuscripts electronically via the journal’s website. Both authors and co-authors can track and monitor their submissions electronically (https://journals.kau.edu.sa/index.php/JRS/index). Accepted manuscripts will be freely available on the journal’s website immediately upon publication. One of our primary objectives on the editorial board is to ensure and maintain rigorous peer review processes while protecting the highest standards of scientific integrity and quality. We are also committed to adhering to ethical guidelines for publication. Our editorial board is composed of distinguished national and international experts from a range of medical rehabilitation-related fields. Our editors will guide the journal’s trajectory and uphold the values of excellence and transparency. Undoubtedly, they will work towards maintaining very high standards, ensuring that the journal’s articles are scientifically reliable and of substantial scholarly value. In this inaugural issue, readers will hopefully enjoy a diverse array of manuscripts presenting the breadth and depth of current medical rehabilitation research. Our goal is to provide valuable insights with the potential to drive progress and inspire the future. These might range from innovative therapeutics and diagnostic procedures to astute critiques and insightful commentaries. The establishment of this journal and the production of the inaugural issue is a historic moment for all researchers and clinicians with an interest in medical rehabilitation. Therefore, on behalf of our editorial board, I would like to express our deepest gratitude to the authors, contributors, and reviewers who have made the launch of J Med Rehab Sci possible. We expect the anticipated success of J Med Rehab Sci to stem from our dedication and passion, significantly contributing to the advancement of medical rehabilitation sciences. As such, I would like to seize this opportunity and invite researchers, clinicians, academicians, and healthcare professionals with a genuine interest in medical rehabilitation sciences to engage with our content, share their discoveries, and participate in enriching and enhancing the field, which will ultimately shape the future of our journal. Together, we hope to shape the next chapter of medical rehabilitation science and practice. Lastly, we want to extend a sincere welcome to all of you to J Med Rehab Sci. We eagerly anticipate a future of groundbreaking findings and significant advancements in the field of medical rehabilitation sciences.